2020
DOI: 10.4103/ijpsym.ijpsym_228_19
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Potential of Ketamine: Opportunities and Challenges

Abstract: Ketamine is a noncompetitive antagonist of the N-methyl-D-aspartate (NMDA) receptor which also interacts with various other receptors that account for its myriad actions. Originally approved as a general anesthetic, it is being explored to be repurposed for numerous other indications such as depressive disorders, suicidal ideation, substance-use disorders, anxiety disorders, chronic pain, refractory status epilepticus, and bronchial asthma exacerbations. Numerous trials are ongoing for the same. The nasal spra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…As mentioned before [26], the improved prefrontal cortex glutamate homeostasis, increased synaptic functioning and enhanced BDNF signaling indicate that esketamine has the potential to be repurposed or further investigated as a treatment for OCD, SUD, PSTD and ED-disorders which have been recorded by some authors to meet the so-called definition of "internalising disorders". These are conditions characterized by internal distress that include the DSM-5 [99] diagnoses of generalized anxiety disorder, social anxiety disorder, MDD, panic disorder and OCD, which are all thought to share the common trait of neuroticism.…”
Section: Possible Advantages Of Ketamine and Esketamine Compared With Current Treatmentsmentioning
confidence: 88%
See 1 more Smart Citation
“…As mentioned before [26], the improved prefrontal cortex glutamate homeostasis, increased synaptic functioning and enhanced BDNF signaling indicate that esketamine has the potential to be repurposed or further investigated as a treatment for OCD, SUD, PSTD and ED-disorders which have been recorded by some authors to meet the so-called definition of "internalising disorders". These are conditions characterized by internal distress that include the DSM-5 [99] diagnoses of generalized anxiety disorder, social anxiety disorder, MDD, panic disorder and OCD, which are all thought to share the common trait of neuroticism.…”
Section: Possible Advantages Of Ketamine and Esketamine Compared With Current Treatmentsmentioning
confidence: 88%
“…Other possible cellular targets of ketamine include opioid (mu, delta and kappa) receptors, and ketamine binding to these receptors has been proposed to contribute to its anti-suicidal and antidepressant effects [16]. A better understanding of the impact of ketamine binding on serotonin, opioid, dopamine and cholinergic receptors [22,26] is needed for a full assessment of the therapeutic potentials of ketamine, especially with regard to mental health disorders. Of note, different preclinical models reported that it is unlikely that NMDA inhibition alone could play a major role in the antidepressant effects of (R,S)-ketamine, opening the door for future studies and major developments [27].…”
Section: Ketamine's Mechanisms Of Actionmentioning
confidence: 99%
“…The high number of articles retrieved as well as the presence of a definite trend for larger and more robust studies emphasise the interest of the scientific community to this research area, which may have significant implications for routine clinical practise. Such awareness likely stems from two important observations: firstly, statins are among the most commonly prescribed medications ( 139 ), hence the discovery that their use is associated with either antidepressant or depressogenic effects would have a very substantial impact on public health; and secondly, the relative lack of any breakthrough development of new antidepressant drugs capable of targeting alternative biological pathways ( 140 ), or that are free from concerns about adverse events and misuse [e.g., ketamine ( 141 )], immediately make the potential use of statins especially appealing.…”
Section: Discussionmentioning
confidence: 99%
“…With a detailed inspection and the application of a power law fit, it is revealed (see Figure 7 ) that for ATC groups, such as J (antibacterials and antivirals), R (nasal preparations) and S (ophthalmologicals), the diversity is smaller compared to such cases as P (anti-parasitic products). The scaling exponent values for some ATC groups align with medical information about the wide range of diseases caused by parasites [ 32 ] for which drugs (with high diversity in targets) of group P are indicated, while the antibacterial and antiviral, ophthalmologic and nasal preparations groups do not follow this high diversity rate [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 94%